Efektivitas Penerapan Video Based Learning di Masa Pandemik Covid-19 pada Pembelajaran Penjas di Sekolah Dasar - Dixon E.M. Taek Bete (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of the study was to find out how to apply video-based learning during the COVID-19 pandemic in physical education learning at SD Inpres Oebaa 4, Kupang City. The research method used is descriptive qualitative naturalistic. The study was conducted on fifth grade students of SD Inpres Oebaa 4 Kupang City for 2 months. Data collection techniques using: observation, interviews and documentation. The data analysis technique was in accordance with the research method, namely descriptive qualitative naturalistic. The results showed that the results of the modified javelin video by students from 21 fifth grade students of SD Inpres Oebaa 4 Kupang City, students who got a score of 4 (very good) were 8 people, students who got a score of 3 (good) were 13 people while a score of 2 (enough) and 1 (less) none. Furthermore, this value is confirmed by the Learning Success Criteria in percent, namely P = 84.5% is in the Effective or successful category. The results of the javelin throwing practice video from 21 fifth grade students of SD Inpres Oebaa 4 Kupang City, students who got a score of 4 (very good) did not exist, students who got a score of 3 (good) were 18 people, students who got a score of 2 (enough) totaling 3 people and a score of 1 (less) does not exist. Furthermore, this value is confirmed by the Learning Success Criteria in percent, namely P = 81.25% is in the Effective or successful category. In conclusion, theapplication of video-based learning during the COVID-19 pandemic is affective in physical education learning at SD Inpres Oebaa 4 Kupang City because the P value is in the Effective/success category. Keywords: Physical Education Learning, Video Based Learning